Koperasi Konsumen, Suatu Obsesi - Shofwan Azhar Solihin (J-Coop : Journal of Co-operative, 2025)
Consumer cooperatives have great potential to be developed in Indonesia, considering that the retail sector is a business that never experiences setbacks. However, until now, cooperatives operating in the financial services sector dominate more than consumer cooperatives. By referring to the consumer cooperative model that has been successful in various countries such as NTUC Fair Price in Singapore, Edeka in Germany, and Coop Mart in Vietnam, this article discusses strategies for developing consumer cooperatives in Indonesia in the face of the dominance of the modern retail business. Consumer cooperatives can be a solution in creating a fairer trading system, providing direct economic benefits to their members, and increasing bargaining power in dealing with suppliers. This research also highlights the challenges faced by consumer cooperatives, including a lack of public understanding, limited access to capital, and unsupportive regulations. By implementing digitalization strategies, collaboration with MSMEs, as well as innovation in membership management and marketing, consumer cooperatives in Indonesia have a great opportunity to develop and contribute to the national economy.